LEGAL PROTECTION AND THE EMPOWERMENT OF THE DISABLED COMMUNITY IN BULELENG REGENCY - Sudiatmaka, Ketut; Artha Windari, Ratna; Sugi Hartono, Made; Ayu Apsari Hadi, I Gusti (Ganesha Law Review, 2020)
This study aims to find out about the protection and empowerment of people with disabilities in Buleleng Regency. In Buleleng regency, either government or private buldings including their public places are not built with fully provided accessibility for persons with disabilities. Furthermore, the persons with disabilities still having trouble to obtain their rights due to social and cultural factors, economic factors, weak policies and law enforcement in favor of disabled and also there is no legal umbrella that clearly regulates the protection and empowerment of persons with disabilities. As for this research is the normative legal study with using qualitatively analysis techniques. The fulfillment of social and economic rights is realized by the government of Buleleng Regency in the form of Social Assistance for Persons with Disabilities with giving an amount of money each month. The persons with disabilities are also trained to be given jobs according to their abilities. There are also Regional Regulations on the protection and fulfillment of the Rights of Persons with Disabilities which is soon be enacted that is include rights and legal protections for persons with disabilities, such as : the right to fullfill equality before the law until intellectual rights are protected.